Implementasi SWOT Digital Marketing Dalam Meningkatkan Penjualan “Show Bakso Malang” di Era New Normal - Irawan Budi Prasetyo; Rina Irawati (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2022)
Abstract The purpose of this study is to determine the internal environmental factors and external environmental factors that are strengths, weaknesses, opportunities and threats in digital marketing, as well as to identify strategies that can be done to increase sales. The object of the research is the Bakso Show, which is a culinary SME that has just been established in Malang. The type of research is descriptive qualitative research with SWOT analysis technique. The technique of checking the validity of the data is using the triangulation technique. The IFAS weighting result is 0.578 and the EFAS weighting result is 0.4625. Both have positive values. The position of Show Bakso’s SWOT is in quadrant 1, namely Progressive. SWOT analysis produces four strategic perspectives, namely SO (Strength-Opportunities), WO (Weakness-Opportunities), ST (Strength-Threats), and WT (Weakness-Threats). Generally, there are 15 digital marketing strategies that can be implemented to increase sales at Show Bakso.